Solid electrolyte and preparation method and application thereof
By using solid electrolytes synthesized by ethanol carbonate polymer monomers, fluoroethylene carbonate polymer monomers and olefinate polymer monomers in lithium-ion batteries, the safety hazards and low energy density of liquid electrolytes are solved. Problem, high safety and high energy density battery performance is achieved.
Patent Information
- Application Number
- CN202411439224.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-11
AI Technical Summary
The liquid electrolyte in existing lithium-ion batteries has safety risks and is low in energy density, so it cannot effectively match the high-voltage positive electrode and the lithium metal negative electrode.
High-safe and high-performance solid electrolytes are synthesized by double bond radical polymerization using preparation materials including ethanolic carbonate polymerized monomers, fluoroethylene carbonate polymerized monomers.
It achieves a solid electrolyte with high safety and high energy density, which can stably match the high-voltage NCM622 positive electrode and lithium metal negative electrode, improving the safety and energy density of the battery.
Smart Images

Figure HDA0005085910150000011 
Figure HDA0005085910150000021 
Figure HDA0005085910150000022
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a solid electrolyte and a preparation method and application thereof. Background Art
[0002] There are still many challenges in the current commercial application of lithium-ion batteries, especially liquid electrolytes, which are flammable and explosive, and pose great safety hazards, which greatly hinder their further development. In addition, the use of graphite negative electrodes results in energy density usually being less than 250Wh / kg, which is far from meeting people's growing energy needs, especially the anxiety about the range of electric vehicles. Lithium metal is regarded as the best choice for lithium battery negative electrodes due to its high theoretical specific capacity and low reduction potential. At the same time, matching with high-voltage positive electrodes can greatly improve the energy density of batteries. Unfortunately, due to the growth of lithium dendrites, unstable high-voltage materials and the decomposition of electrolytes, current commercial electrolytes cannot be adapted to these electrode materials. Therefore, it is necessary to develop a highly safe electrolyte that can match high-voltage positive electrodes and lithium metal negative electrodes.
[0003] Solid polymer electrolytes are a promising electrolyte that has no risk of leakage, is lightweight and easy to prepare, and can solve the above-mentioned shortcomings of liquid electrolytes. However, most polymer electrolytes still have many defects, such as low room temperature ion conductivity, low migration number, poor high-voltage performance, instability to lithium metal, and the ability of some materials to burn. These defects have seriously hindered the development and application of solid electrolytes. Summary of the invention
[0004] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a solid electrolyte.
[0005] A second object of the present invention is to provide a method for preparing the above-mentioned solid electrolyte.
[0006] A third object of the present invention is to provide a solid-state battery.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present invention provides a solid electrolyte, comprising an electrolyte salt and a polymer; the raw materials for preparing the polymer include ethylene carbonate polymer monomers, fluoroethylene carbonate polymer monomers and ethylene phosphate polymer monomers.
[0009] The present invention adopts the reaction of raw materials including carbonate ester polymerization monomers, fluorocarbonate ester polymerization monomers and phosphoester polymerization monomers to prepare the polymer, wherein the carbonate ester segment in the polymer can ensure the rapid conduction of alkali metal ions (lithium ions, sodium ions or potassium ions); the fluorocarbonate ester segment can provide sufficient fluorine source to ensure the formation of a good positive and negative electrode interface; the phosphoester segment provides a flame retardant group to ensure that the prepared solid electrolyte is non-flammable and has high safety. The polymer in the present invention organically integrates the carbonate ester polymerization monomer, the fluorocarbonate ester polymerization monomer and the phosphoester polymerization monomer through a double-bond free radical polymerization method to synthesize a high-safety and high-performance solid electrolyte for high-voltage alkali metal batteries, such as high-voltage lithium metal batteries, high-voltage sodium metal batteries, and high-voltage potassium metal batteries.
[0010] Preferably, the solid electrolyte further comprises a separator; the electrolyte salt and the polymer are distributed on the separator.
[0011] Preferably, the diaphragm is selected from at least one of a ceramic-coated polypropylene diaphragm, a glass fiber diaphragm, a polypropylene diaphragm, a polyethylene diaphragm, and a cellulose acetate diaphragm.
[0012] Preferably, the ceramic-coated polypropylene diaphragm is an alumina-coated polypropylene diaphragm.
[0013] Preferably, the electrolyte salt is a lithium salt, a sodium salt or a potassium salt.
[0014] Preferably, the lithium salt is selected from at least one of LiTFSI, LiFSI, LiPF6, LiClO4, LiCF3SO3, LiBOB, and LiBF4.
[0015] Preferably, the sodium salt is selected from at least one of NaTFSI, NaFSI, NaPF6, NaClO4, NaCF3SO3, NaBOB, and NaBF4.
[0016] Preferably, the potassium salt is selected from at least one of KTFSI, KFSI, KPF6, KClO4, KCF3SO3, KBOB, and KBF4.
[0017] Preferably, the olefin carbonate polymerization monomer is selected from at least one of vinyl ethylene carbonate, allyl methyl carbonate, allyl ethyl carbonate, diallyl pyrocarbonate, dimethyl allyl carbonate and vinylene carbonate.
[0018] Preferably, the fluoroalkylene carbonate polymer monomer is at least one selected from 2,2,3,4,4,4-hexafluorobutyl methacrylate, allyl perfluoropentanoate, allyl perfluorononanoate, allyl trifluoroacetate, and hexafluorobutyl acrylate.
[0019] Preferably, the phosphate ester polymerization monomer is selected from at least one of triallyl phosphate, 2-allyl-diethyl phosphate, and allyl diethyl phosphate.
[0020] Preferably, the raw materials for preparing the polymer further include an initiator, and based on the total mass percentage of the ethylene carbonate polymer monomers, the fluoroethylene carbonate polymer monomers and the ethylene phosphate polymer monomers as 100%, the mass percentage of the initiator is 0.1-1%.
[0021] Preferably, the molar ratio of the alkylene carbonate polymer monomer, the alkylene fluoride carbonate polymer monomer and the alkylene phosphate polymer monomer is 1:(0.05-0.15):(0.1-0.2).
[0022] Preferably, the molar ratio of the fluoroalkylene carbonate polymer monomer to the alkylene phosphate polymer monomer is 1:(1-2).
[0023] The second aspect of the present invention provides a method for preparing the solid electrolyte according to the first aspect of the present invention, comprising the following steps:
[0024] S1: mixing the raw materials for preparing the polymer and the electrolyte salt to obtain a precursor solution;
[0025] S2: heating the precursor solution to perform a polymerization reaction; or, loading the precursor solution on a diaphragm, and heating the precursor solution to perform an in-situ polymerization reaction on the diaphragm.
[0026] The preparation method of the present invention can directly heat the precursor solution to obtain a solid electrolyte, or can adopt an in-situ polymerization method to make the raw materials for preparing the polymer in-situ polymerize on the diaphragm to form a polymer; compared with directly heating the precursor solution to obtain a solid electrolyte, the method of in-situ polymerization of the precursor solution on the diaphragm can achieve a closer contact between the positive and negative electrodes of the battery and the solid electrolyte, and the formed polymer can also uniformly coat the electrolyte salt and load it on the diaphragm.
[0027] Preferably, in the precursor solution, the concentration of the electrolyte salt is 0.5 to 2 mol / L.
[0028] Preferably, the temperature of the in-situ polymerization reaction is 50-80°C.
[0029] Preferably, the in-situ polymerization reaction time is 2 to 12 hours.
[0030] Preferably, the preparation method is carried out under an inert atmosphere with a water content of less than 1 ppm and an oxygen content of less than 1 ppm.
[0031] Preferably, the inert atmosphere is selected from at least one of nitrogen, argon and xenon; more preferably, the inert gas is selected from argon.
[0032] Preferably, the mass of the electrolyte salt is 10-40% of the total mass of the raw materials for preparing the polymer.
[0033] The third aspect of the present invention provides a solid-state battery, comprising the solid-state electrolyte described in the first aspect of the present invention.
[0034] Preferably, the positive electrode active material of the solid-state battery includes at least one of NCM622, NCM811, and LFP positive electrode materials. NCM positive electrode material is a high-nickel ternary lithium-ion battery positive electrode material LiNi 1-x-y Co x Mn y O2(NCM).
[0035] Preferably, the NCM positive electrode material comprises LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM111), LiNi 0.4 Co 0.2 Mn 0.4 O2(NCM424), LiNi 0.5 Co 0.3 Mn 0.2 O2(NCM532), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 At least one of O2 (NCM811).
[0036] Preferably, the charging voltage of the solid-state battery is ≥4.3V.
[0037] The beneficial effects of the present invention are: the solid electrolyte in the present invention has high ionic conductivity and electrochemical stability, and has higher safety and energy density compared to commercial liquid electrolytes. After the assembled soft-pack battery passes the needle puncture test, there is no bulging, gas production or combustion explosion. In addition, the solid electrolyte in the present invention can achieve a wide electrochemical stability window and relatively stable cycle performance while ensuring high ionic conductivity, and has a high energy density. In addition, the solid electrolyte in the present invention can stably match the high-voltage NCM622 positive electrode and the alkali metal negative electrode, effectively improving the safety and energy density of the battery, and contributing to the development of power batteries and electrochemical energy storage research.
[0038] The preparation method of the present invention is simple and easy to operate. By in-situ polymerizing the raw materials for preparing the polymer on the diaphragm to form a solid electrolyte, close contact between the positive and negative electrodes of the battery and the solid electrolyte can be achieved. In addition, the preparation method of the present invention first prepares a precursor solution, then assembles it into a battery, and uses an in-situ polymerization method for curing synthesis, which can match the process of modern commercial lithium-ion battery production and is conducive to the commercial application of the preparation method of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the infrared test spectrum of the solid electrolyte in Example 1.
[0040] Figure 2 The linear voltammetry curves of the solid electrolytes of Example 1 and Comparative Example 1 are shown.
[0041] Figure 3 This is a combustion comparison experiment diagram of the solid electrolyte of Example 1 and Comparative Example 1.
[0042] Figure 4 Graph showing the cycling performance of Li||Li batteries assembled with the solid electrolytes of Example 1 and Comparative Example 1 at room temperature.
[0043] Figure 5 It is a cycle performance curve diagram of the solid-state batteries of Example 1 and Comparative Example 1 at room temperature.
[0044] Figure 6 This is a surface morphology test diagram of the diaphragm in Example 1 before and after in-situ polymerization. DETAILED DESCRIPTION
[0045] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0046] In some embodiments of the present invention, the present invention provides a solid electrolyte, including an electrolyte salt and a polymer; the raw materials for preparing the polymer include carbonate ester polymer monomers, fluorocarbonate ester polymer monomers and phosphate ester polymer monomers. The present invention adopts the reaction of raw materials including carbonate ester polymer monomers, fluorocarbonate ester polymer monomers and phosphate ester polymer monomers to prepare the polymer, wherein the carbonate ester segment in the polymer can ensure the rapid conduction of alkali metal ions (lithium ions, sodium ions or potassium ions); the fluorocarbonate ester segment can provide sufficient fluorine source to ensure the formation of a good positive and negative electrode interface; the phosphate ester segment provides a flame retardant group to ensure that the prepared solid electrolyte is non-flammable and has high safety. The polymer in the present invention organically integrates the carbonate ester polymer monomers, fluorocarbonate ester polymer monomers and phosphate ester polymer monomers through the method of double bond free radical polymerization to synthesize a high-safety and high-performance solid electrolyte for high-voltage alkali metal batteries.
[0047] In some embodiments of the present invention, the solid electrolyte further includes a separator; the electrolyte salt and the polymer are distributed on the separator.
[0048] In some embodiments of the present invention, the separator is selected from at least one of a ceramic-coated polypropylene separator, a glass fiber separator, a polypropylene separator, a polyethylene separator, and a cellulose acetate separator. In some embodiments of the present invention, the separator is a ceramic-coated polypropylene separator. In the present invention, the separator can provide support for the polymer and the electrolyte salt, so that the electrolyte salt and the polymer are evenly distributed on the surface of the separator.
[0049] In some embodiments of the present invention, the ceramic coated polypropylene diaphragm is an alumina coated polypropylene diaphragm.
[0050] In some embodiments of the present invention, the electrolyte salt is a lithium salt, a sodium salt or a potassium salt.
[0051] In some embodiments of the present invention, the lithium salt is selected from at least one of LiTFSI, LiFSI, LiPF6, LiClO4, LiCF3SO3, LiBOB, and LiBF4. In some embodiments of the present invention, the lithium salt is LiTFSI.
[0052] In some embodiments of the present invention, the sodium salt is selected from at least one of NaTFSI, NaFSI, NaPF6, NaClO4, NaCF3SO3, NaBOB, and NaBF4. In some embodiments of the present invention, the sodium salt is NaTFSI.
[0053] In some embodiments of the present invention, the potassium salt is selected from at least one of KTFSI, KFSI, KPF6, KClO4, KCF3SO3, KBOB, and KBF4. In some embodiments of the present invention, the potassium salt is KTFSI.
[0054] In some embodiments of the present invention, the olefin carbonate polymer monomer is selected from at least one of vinyl ethylene carbonate, allyl methyl carbonate, allyl ethyl carbonate, diallyl pyrocarbonate, dimethyl allyl carbonate, and vinylene carbonate. In some embodiments of the present invention, the olefin carbonate polymer monomer is vinyl ethylene carbonate. In the present invention, the introduction of the olefin carbonate polymer monomer can make the prepared solid electrolyte have a higher lithium ion mobility, ensuring efficient lithium ion transmission.
[0055] In some embodiments of the present invention, the fluorocarbonate polymerized monomer is selected from at least one of 2,2,3,4,4,4-hexafluorobutyl methacrylate, allyl perfluoropentanoate, allyl perfluorononanoate, allyl trifluoroacetate, and hexafluorobutyl acrylate. In some embodiments of the present invention, the fluorocarbonate polymerized monomer is 2,2,3,4,4,4-hexafluorobutyl methacrylate. In the present invention, the introduction of the fluorocarbonate polymerized monomer enables the prepared solid electrolyte to have more fluorine sources, which can ensure that the positive and negative electrodes of the battery form a good contact interface with the surface of the solid electrolyte, which is beneficial to improving the performance of the battery.
[0056] In some embodiments of the present invention, the phosphoenyl ester polymer monomer is selected from at least one of triallyl phosphate, 2-propenyl-diethyl phosphate, and allyl diethyl phosphate. In some embodiments of the present invention, the phosphoenyl ester polymer monomer is triallyl phosphate. The introduction of the phosphoenyl ester polymer monomer enables the prepared solid electrolyte to have excellent flame retardant properties, thereby improving the safety of the battery and avoiding fire or explosion of the battery during use or charging.
[0057] In some embodiments of the present invention, the raw materials for preparing the polymer further include an initiator, which is used to cause the olefin carbonate polymer monomer, the fluorinated olefin carbonate polymer monomer and the olefin phosphate polymer monomer to undergo a polymerization reaction, thereby forming a polymer.
[0058] In some embodiments of the present invention, the mass percentage of the initiator is 0.1-1%, based on the total mass percentage of the carbonate ester polymer monomer, the fluorocarbonate ester polymer monomer and the phosphate ester polymer monomer as 100%. In some embodiments of the present invention, the mass percentage of the initiator is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%. If the amount of initiator is too little, the reaction is incomplete, so that the solid electrolyte contains more impurities, which is not conducive to improving the battery performance. If the amount of initiator is too much, the initiator residue will affect the performance of the battery, which is not conducive to improving the battery performance.
[0059] In some embodiments of the present invention, the initiator is selected from at least one of azobisisobutyronitrile, benzoyl peroxide, di-tert-butyl peroxide, cumene hydroperoxide, lauroyl peroxide, ammonium persulfate, potassium persulfate, and azobisisoheptanenitrile. In some embodiments of the present invention, the initiator is azobisisobutyronitrile.
[0060] In some embodiments of the present invention, the molar ratio of the carbonate ester polymerization monomer, the fluorocarbonate ester polymerization monomer and the phosphate ester polymerization monomer is 1: (0.08-0.15): (0.1-0.2), for example, it can be selected from 1:0.08:0.1, 1:0.15:0.1, 1:0.15:0.2, 1:0.08:0.2, 1:0.1:0.15, 1:0.1:0.2, 1:0.1:0.1, 1:0.12:0.15.
[0061] In some embodiments of the present invention, the molar ratio of the fluorocarbonate polymer monomer to the phosphate polymer monomer is 1:(1-2), for example, it can be selected from 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2.
[0062] In some embodiments of the present invention, the present invention also provides a method for preparing the above-mentioned solid electrolyte, comprising the following steps:
[0063] S1: mixing the raw materials for preparing the polymer and the electrolyte salt to obtain a precursor solution;
[0064] S2: heating the precursor solution to perform a polymerization reaction; or, loading the precursor solution on a diaphragm, and heating the precursor solution to perform an in-situ polymerization reaction on the diaphragm.
[0065] The preparation method of the present invention can directly heat the precursor solution to obtain a solid electrolyte, or can use an in-situ polymerization method to make the raw materials for preparing the polymer polymerize in situ on the diaphragm to form a polymer; relative to directly heating the precursor solution to obtain a solid electrolyte, the method of in-situ polymerization of the precursor solution on the diaphragm can achieve a closer contact between the positive and negative electrodes of the battery and the solid electrolyte, and the formed polymer can also uniformly coat the electrolyte salt and load it on the diaphragm. In some embodiments of the present invention, the solid electrolyte in the present invention is prepared by a preparation method comprising the following steps:
[0066] S1: mixing olefin carbonate polymer monomers, olefin fluoride carbonate polymer monomers, olefin phosphate polymer monomers, an initiator and an electrolyte salt to obtain a precursor solution;
[0067] S2: Loading the precursor solution on the diaphragm, then assembling into a battery, heating the precursor solution to make it undergo an in-situ polymerization reaction on the diaphragm, disassembling the battery, and obtaining the solid electrolyte.
[0068] After the precursor solution is loaded on the diaphragm, the present invention can directly heat the reaction in the glove box to make the precursor solution undergo an in-situ polymerization reaction on the diaphragm, or, after the precursor solution is loaded on the diaphragm, it is assembled into a battery, and then the battery is heated to make the precursor solution in the battery undergo an in-situ polymerization reaction on the diaphragm. At this time, the solid electrolyte is formed in the battery, and the solid electrolyte is formed by reaction between the positive and negative electrodes, and has a better contact interface with the positive and negative electrodes. The battery can be used directly, or the battery can be disassembled, the solid electrolyte is taken out, and the solid electrolyte is assembled into a new battery with other positive and negative electrodes before use.
[0069] The preparation method of the present invention adopts an in-situ polymerization method, so that the raw materials for preparing the polymer are in-situ polymerized on the diaphragm to form a polymer, which can achieve close contact between the positive and negative electrodes of the battery and the solid electrolyte. At the same time, the formed polymer can also uniformly coat the electrolyte salt and load it on the diaphragm.
[0070] In some embodiments of the present invention, the concentration of the electrolyte salt in the precursor solution is 0.5-2 mol / L, for example: it can be selected from 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, and 2 mol / L.
[0071] In some embodiments of the present invention, the temperature of the in situ polymerization reaction is 50-80°C, for example, can be selected from 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, and 80°C.
[0072] In some embodiments of the present invention, the time of the in-situ polymerization reaction is 2 to 12 hours, for example, can be selected from 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, and 12 hours.
[0073] In some embodiments of the present invention, the preparation method is carried out under an inert atmosphere with a water content of less than 1 ppm and an oxygen content of less than 1 ppm.
[0074] In some embodiments of the present invention, the inert atmosphere is selected from at least one of nitrogen, argon, and xenon; in some embodiments of the present invention, the inert gas is selected from argon.
[0075] In some embodiments of the present invention, the mass of the electrolyte salt is 10-40% of the total mass of the raw materials for preparing the polymer, for example, it can be selected from 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%.
[0076] In some embodiments of the present invention, the present invention further provides a solid-state battery, the electrolyte of which adopts the above-mentioned solid-state electrolyte.
[0077] In some embodiments of the present invention, the positive electrode active material of the solid-state battery includes at least one of NCM622, NCM811, and LFP positive electrode materials.
[0078] In some embodiments of the present invention, the solid-state battery further includes a positive electrode and a negative electrode, and the positive electrode active material of the positive electrode is an NCM positive electrode material.
[0079] In some embodiments of the present invention, the NCM positive electrode material includes LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM111), LiNi 0.4 Co 0.2 Mn 0.4 O2(NCM424), LiNi 0.5Co 0.3 Mn 0.2 O2(NCM532), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 At least one of O2 (NCM811).
[0080] In some embodiments of the present invention, the charging voltage of the solid-state battery is ≥4.3V.
[0081] In some embodiments of the present invention, the negative electrode is lithium metal, sodium metal, or potassium metal.
[0082] The implementation of the present invention is further described in detail below with reference to specific embodiments:
[0083] The solid electrolytes and solid batteries containing the solid electrolytes in Examples 1 to 8 of the present invention and Comparative Example 1 were prepared in a glove box filled with argon gas with a water content of less than 1 ppm and an oxygen content of less than 1 ppm.
[0084] Example 1
[0085] This example provides a solid-state battery, which is prepared by a preparation method comprising the following steps:
[0086] (1) preparing a precursor solution: after 1 mol of vinyl ethylene carbonate, 0.1 mol of 2,2,3,4,4,4-hexafluorobutyl methacrylate and 0.15 mol of triallyl phosphate are uniformly stirred, 0.1% by mass of azobisisobutyronitrile (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) and 20% by mass of LiTFSI (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) are added, and stirring is continued until the mixture is completely dissolved to obtain a precursor solution;
[0087] (2) Preparation of positive electrode sheet: First, NCM622 powder, conductive carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. After adding N-methylpyrrolidone, a stirrer was used to mix and stir them evenly to form a slurry. The slurry was then scraped onto aluminum foil and dried in an oven at 80°C for 12 h. The slurry was compacted with a tablet press and cut into positive electrode sheets with a diameter of 12 mm. The slurry was then placed in a vacuum drying oven at 80°C for 12 h, weighed, and placed in a glove box for later use.
[0088] (3) Assembling a solid-state lithium metal battery: first, place the positive electrode sheet in the middle of the positive electrode shell, then place the diaphragm (alumina-coated polypropylene diaphragm purchased from Shenzhen Kejing Zhida Technology Co., Ltd.), then drop 50 μL of the precursor solution prepared in step (1), place the lithium sheet, steel sheet, gasket and negative electrode shell, and finally press the battery with a battery sealing machine to assemble it into a CR2032 battery;
[0089] (4) The assembled battery was placed in an oven and heated at 70° C. for 6 hours for in-situ polymerization, so that the precursor solution was cured in situ, and the CR2032 battery was subjected to corresponding tests.
[0090] Example 2
[0091] This example provides a solid-state battery, which is prepared by a preparation method comprising the following steps:
[0092] (1) preparing a precursor solution: after 1 mol of vinyl ethylene carbonate, 0.1 mol of 2,2,3,4,4,4-hexafluorobutyl methacrylate and 0.15 mol of triallyl phosphate are uniformly stirred, 0.1% by mass of azobisisobutyronitrile (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) and 10% by mass of LiTFSI (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) are added, and stirring is continued until the mixture is completely dissolved to obtain a precursor solution;
[0093] (2) Preparation of positive electrode sheet: First, NCM622 powder, conductive carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. After adding N-methylpyrrolidone, a stirrer was used to mix and stir them evenly to form a slurry. The slurry was then scraped onto aluminum foil and dried in an oven at 80°C for 12 h. The slurry was compacted with a tablet press and cut into positive electrode sheets with a diameter of 12 mm. The slurry was then placed in a vacuum drying oven at 80°C for 12 h, weighed, and placed in a glove box for later use.
[0094] (3) Assembling a solid-state lithium metal battery: first, place the positive electrode sheet in the middle of the positive electrode shell, then place the diaphragm (alumina-coated polypropylene diaphragm purchased from Shenzhen Kejing Zhida Technology Co., Ltd.), then drop 50 μL of the precursor solution prepared in step (1), place the lithium sheet, steel sheet, gasket and negative electrode shell, and finally press the battery with a battery sealing machine to assemble it into a CR2032 battery;
[0095] (4) The assembled battery was placed in an oven at 70° C. and heated for 6 hours for in-situ polymerization to cure the precursor solution in situ, and then the CR2032 battery was subjected to corresponding tests.
[0096] Example 3
[0097] This example provides a solid-state battery, which is prepared by a preparation method comprising the following steps:
[0098] (1) preparing a precursor solution: after 1 mol of vinyl ethylene carbonate, 0.1 mol of 2,2,3,4,4,4-hexafluorobutyl methacrylate and 0.15 mol of triallyl phosphate are uniformly stirred, 0.1% by mass of azobisisobutyronitrile (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) and 30% by mass of LiTFSI (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) are added, and stirring is continued until the mixture is completely dissolved to obtain a precursor solution;
[0099] (2) Preparation of positive electrode sheet: First, NCM622 powder, conductive carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. After adding N-methylpyrrolidone, a stirrer was used to mix and stir them evenly to form a slurry. The slurry was then scraped onto aluminum foil and dried in an oven at 80°C for 12 h. The slurry was compacted with a tablet press and cut into positive electrode sheets with a diameter of 12 mm. The slurry was then placed in a vacuum drying oven at 80°C for 12 h, weighed, and placed in a glove box for later use.
[0100] (3) Assembling a solid-state lithium metal battery: first, place the positive electrode sheet in the middle of the positive electrode shell, then place the diaphragm (alumina-coated polypropylene diaphragm purchased from Shenzhen Kejing Zhida Technology Co., Ltd.), then drop 50 μL of the precursor solution prepared in step (1), place the lithium sheet, steel sheet, gasket and negative electrode shell, and finally press the battery with a battery sealing machine to assemble it into a CR2032 battery;
[0101] (4) The assembled battery was placed in an oven at 70° C. and heated for 6 hours for in-situ polymerization to cure the precursor solution in situ, and then the CR2032 battery was subjected to corresponding tests.
[0102] Example 4
[0103] This example provides a solid-state battery, which is prepared by a preparation method comprising the following steps:
[0104] (1) preparing a precursor solution: after 1 mol of vinyl ethylene carbonate, 0.1 mol of 2,2,3,4,4,4-hexafluorobutyl methacrylate and 0.15 mol of triallyl phosphate are uniformly stirred, 0.1% by mass of azobisisobutyronitrile (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) and 40% by mass of LiTFSI (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) are added, and stirring is continued until the mixture is completely dissolved to obtain a precursor solution;
[0105] (2) Preparation of positive electrode sheet: First, NCM622 powder, conductive carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. After adding N-methylpyrrolidone, a stirrer was used to mix and stir them evenly to form a slurry. The slurry was then scraped onto aluminum foil and dried in an oven at 80°C for 12 h. The slurry was compacted with a tablet press and cut into positive electrode sheets with a diameter of 12 mm. The slurry was then placed in a vacuum drying oven at 80°C for 12 h, weighed, and placed in a glove box for later use.
[0106] (3) Assembling a solid-state lithium metal battery: first, place the positive electrode sheet in the middle of the positive electrode shell, then place the diaphragm (aluminum oxide-coated polypropylene diaphragm purchased from Shenzhen Kejing Zhida Technology Co., Ltd.), then drop 50 μL of the precursor solution obtained in step (1), place the lithium sheet, steel sheet, gasket and negative electrode shell, and finally press the battery with a battery sealing machine to assemble it into a CR2032 battery;
[0107] (4) The assembled battery was placed in an oven at 70° C. and heated for 6 hours for in-situ polymerization to cure the precursor solution in situ, and then the CR2032 battery was subjected to corresponding tests.
[0108] Example 5
[0109] This example provides a solid-state battery, which is prepared by a preparation method comprising the following steps:
[0110] (1) preparing a precursor solution: after 1 mol of vinyl ethylene carbonate, 0.05 mol of 2,2,3,4,4,4-hexafluorobutyl methacrylate and 0.15 mol of triallyl phosphate are uniformly stirred, 0.1% by mass of azobisisobutyronitrile (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) and 20% by mass of LiTFSI (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) are added, and stirring is continued until the mixture is completely dissolved to obtain a precursor solution;
[0111] (2) Preparation of positive electrode sheet: First, NCM622 powder, conductive carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. After adding N-methylpyrrolidone, a stirrer was used to mix and stir them evenly to form a slurry. The slurry was then scraped onto aluminum foil and dried in an oven at 80°C for 12 h. The slurry was compacted with a tablet press and cut into positive electrode sheets with a diameter of 12 mm. The slurry was then placed in a vacuum drying oven at 80°C for 12 h, weighed, and placed in a glove box for later use.
[0112] (3) Assembling a solid-state lithium metal battery: first, place the positive electrode sheet in the middle of the positive electrode shell, then place the diaphragm (alumina-coated polypropylene diaphragm purchased from Shenzhen Kejing Zhida Technology Co., Ltd.), then drop 50 μL of the precursor solution prepared in step (1), place the lithium sheet, steel sheet, gasket and negative electrode shell, and finally press the battery with a battery sealing machine to assemble it into a CR2032 battery;
[0113] (4) The assembled battery was placed in an oven at 70° C. and heated for 6 hours for in-situ polymerization to cure the precursor solution in situ, and then the CR2032 battery was subjected to corresponding tests.
[0114] Example 6
[0115] This example provides a solid-state battery, which is prepared by a preparation method comprising the following steps:
[0116] (1) preparing a precursor solution: after 1 mol of vinyl ethylene carbonate, 0.15 mol of 2,2,3,4,4,4-hexafluorobutyl methacrylate and 0.15 mol of triallyl phosphate are uniformly stirred, 0.1% by mass of azobisisobutyronitrile (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) and 20% by mass of LiTFSI (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) are added, and stirring is continued until the mixture is completely dissolved to obtain a precursor solution;
[0117] (2) Preparation of positive electrode sheet: First, NCM622 powder, conductive carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. After adding N-methylpyrrolidone, a stirrer was used to mix and stir them evenly to form a slurry. The slurry was then scraped onto aluminum foil and dried in an oven at 80°C for 12 h. The slurry was compacted with a tablet press and cut into positive electrode sheets with a diameter of 12 mm. The slurry was then placed in a vacuum drying oven at 80°C for 12 h, weighed, and placed in a glove box for later use.
[0118] (3) Assembling a solid-state lithium metal battery: first, place the positive electrode sheet in the middle of the positive electrode shell, then place the diaphragm (alumina-coated polypropylene diaphragm purchased from Shenzhen Kejing Zhida Technology Co., Ltd.), then drop 50 μL of the precursor solution prepared in step (1), place the lithium sheet, steel sheet, gasket and negative electrode shell, and finally press the battery with a battery sealing machine to assemble it into a CR2032 battery;
[0119] (4) The assembled battery was placed in an oven at 70° C. and heated for 6 hours for in-situ polymerization to cure the precursor solution in situ, and then the CR2032 battery was subjected to corresponding tests.
[0120] Example 7
[0121] This example provides a solid-state battery, which is prepared by a preparation method comprising the following steps:
[0122] (1) preparing a precursor solution: after 1 mol of vinyl ethylene carbonate, 0.1 mol of 2,2,3,4,4,4-hexafluorobutyl methacrylate and 0.1 mol of triallyl phosphate are uniformly stirred, 0.1% by mass of azobisisobutyronitrile (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) and 20% by mass of LiTFSI (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) are added, and stirring is continued until the mixture is completely dissolved to obtain a precursor solution;
[0123] (2) Preparation of positive electrode sheet: First, NCM622 powder, conductive carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. After adding N-methylpyrrolidone, a stirrer was used to mix and stir them evenly to form a slurry. The slurry was then scraped onto aluminum foil and dried in an oven at 80°C for 12 h. The slurry was compacted with a tablet press and cut into positive electrode sheets with a diameter of 12 mm. The slurry was then placed in a vacuum drying oven at 80°C for 12 h, weighed, and placed in a glove box for later use.
[0124] (3) Assembling a solid-state lithium metal battery: first, place the positive electrode sheet in the middle of the positive electrode shell, then place the diaphragm (alumina-coated polypropylene diaphragm purchased from Shenzhen Kejing Zhida Technology Co., Ltd.), then drop 50 μL of the precursor solution prepared in step (1), place the lithium sheet, steel sheet, gasket and negative electrode shell, and finally press the battery with a battery sealing machine to assemble it into a CR2032 battery;
[0125] (4) The assembled battery was placed in an oven at 70° C. and heated for 6 hours for in-situ polymerization to cure the precursor solution in situ, and then the CR2032 battery was subjected to corresponding tests.
[0126] Example 8
[0127] This example provides a solid-state battery, which is prepared by a preparation method comprising the following steps:
[0128] (1) preparing a precursor solution: after 1 mol of vinyl ethylene carbonate, 0.1 mol of 2,2,3,4,4,4-hexafluorobutyl methacrylate and 0.2 mol of triallyl phosphate are uniformly stirred, 0.1% by mass of azobisisobutyronitrile (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) and 20% by mass of LiTFSI (based on the total mass percentage of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate being 100%) are added, and stirring is continued until the mixture is completely dissolved to obtain a precursor solution;
[0129] (2) Preparation of positive electrode sheet: First, NCM622 powder, conductive carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. After adding N-methylpyrrolidone, a stirrer was used to mix and stir them evenly to form a slurry. The slurry was then scraped onto aluminum foil and dried in an oven at 80°C for 12 h. The slurry was compacted with a tablet press and cut into positive electrode sheets with a diameter of 12 mm. The slurry was then placed in a vacuum drying oven at 80°C for 12 h, weighed, and placed in a glove box for later use.
[0130] (3) Assembling a solid-state lithium metal battery: first, place the positive electrode sheet in the middle of the positive electrode shell, then place the diaphragm (alumina-coated polypropylene diaphragm purchased from Shenzhen Kejing Zhida Technology Co., Ltd.), then drop 50 μL of the precursor solution prepared in step (1), place the lithium sheet, steel sheet, gasket and negative electrode shell, and finally press the battery with a battery sealing machine to assemble it into a CR2032 battery;
[0131] (4) The assembled battery was placed in an oven at 70° C. and heated for 6 hours for in-situ polymerization to cure the precursor solution in situ, and then the CR2032 battery was subjected to corresponding tests.
[0132] Comparative Example 1
[0133] This example provides a solid-state battery, which is prepared by a preparation method comprising the following steps:
[0134] (1) preparing a precursor solution: adding 0.1% by mass of azobisisobutyronitrile (based on the mass of vinyl ethylene carbonate) and 20% by mass of LiTFSI (based on the mass of vinyl ethylene carbonate) to 1 mol of vinyl ethylene carbonate, and continuing to stir until completely dissolved to obtain a precursor solution;
[0135] (2) Preparation of positive electrode sheet: First, NCM622 powder, conductive carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. After adding N-methylpyrrolidone, a stirrer was used to mix and stir them evenly to form a slurry. The slurry was then scraped onto aluminum foil and dried in an oven at 80°C for 12 h. The slurry was compacted with a tablet press and cut into positive electrode sheets with a diameter of 12 mm. The slurry was then placed in a vacuum drying oven at 80°C for 12 h, weighed, and placed in a glove box for later use.
[0136] (3) Assembling a solid-state lithium metal battery: first, place the positive electrode sheet in the middle of the positive electrode shell, then place the diaphragm (alumina-coated polypropylene diaphragm purchased from Shenzhen Kejing Zhida Technology Co., Ltd.), then drop 50 μL of the precursor solution prepared in step (1), place the lithium sheet, steel sheet, gasket and negative electrode shell, and finally press the battery with a battery sealing machine to assemble it into a CR2032 battery;
[0137] (4) The assembled battery was placed in an oven at 70° C. and heated for 6 hours for in-situ polymerization to cure the precursor solution in situ, and then the CR2032 battery was subjected to corresponding tests.
[0138] The precursor solutions in Examples 1 to 8 and Comparative Example 1 were coated on the surface of a substrate and heated to 70° C. for polymerization for 6 hours. The substrate was removed to obtain solid electrolytes in Examples 1 to 8 and Comparative Example 1 for performance testing.
[0139] Performance Testing:
[0140] The infrared test spectra of the solid electrolyte and its raw materials of Test Example 1 are as follows: Figure 1 As shown, it can be found that the characteristic peak of the carbon-carbon double bond disappears, indicating that the polymerization reaction is complete. The linear voltammetric curves (LSV) of the solid electrolytes in Example 1 and Comparative Example 1 are tested respectively. The specific test results are shown in Figure 2 As shown. Figure 2 It can be seen that the oxidation potential of the solid electrolyte in Example 1 is 5.15 V, which is significantly higher than the solid electrolyte of Comparative Example 1 which does not contain fluorine and phosphorus groups (whose oxidation potential is 4.37 V), indicating that the present invention introduces fluorine groups and phosphorus groups into the solid electrolyte, which can effectively improve the antioxidant performance of the positive electrode side of the solid electrolyte and widen the voltage window of the solid-state lithium metal battery.
[0141] The solid electrolytes in Example 1 and Comparative Example 1 were subjected to a combustion test. The specific test diagram is shown in FIG. Figure 3 shown by Figure 3It can be seen that the solid electrolyte in Comparative Example 1 does not contain phosphorus-containing groups, and it will burn violently when it encounters an open flame, indicating that it still has great safety hazards. However, the solid electrolyte in Example 1 contains phosphorus-containing groups, and when it encounters an open flame, it does not burn and its shape and performance remain intact, indicating that the solid electrolyte in the present invention has excellent non-flammability.
[0142] The method in Example 1 and Comparative Example 1 was used to install the Li||Li symmetrical battery in situ, and then the cycle performance was tested. The test current was 0.2 mA / cm 2 , the specific test results are as follows Figure 4 As shown. Figure 4 It can be seen that at 0.2mA / cm 2 At a current density of , the Li||Li symmetric battery in Comparative Example 1 short-circuited after cycling for 650 h, while the Li||Li symmetric battery in Example 1 could stably cycle for more than 1000 h, and the overpotential could still remain stable, further indicating that the present invention can effectively improve the stability of the lithium metal negative electrode side by introducing fluorine-containing groups and phosphorus-containing groups into the solid electrolyte.
[0143] The solid electrolytes in Example 1 and Comparative Example 1 were assembled into Li||NCM622 CR2032 batteries (i.e., the solid-state batteries in Example 1 and Comparative Example 1), and then the cycle performance of the batteries at a rate of 0.5C was tested. The specific test results are as follows: Figure 5 As shown. Figure 5 It can be seen that at a rate of 0.5C, the discharge capacity of the Li||NCM622 full battery in Example 1 can reach 150.1mAh / g, and the coulombic efficiency is 99.8%, while the discharge capacity of the Li||NCM622 full battery in Comparative Example 1 is only 107.8mAh / g, and the coulombic efficiency is 99.5%. In addition, the cycle stability of the Li||NCM622 full battery in Example 1 is much higher than that in Comparative Example 1. When the cut-off charging voltage is 4.3V, when the cycle reaches 100 cycles, the capacity retention rate of Example 1 is 80.5%, while the capacity retention rate of Comparative Example 1 is only 67.2%.
[0144] The surface morphology of the membrane in Example 1 before and after in-situ polymerization was tested respectively. The test results are as follows: Figure 6 As shown, Figure 6 (a) and Figure 6 (b) The surface morphology of the membrane before and after polymerization. Figure 6It can be seen that vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate can fill the gaps on the surface of the diaphragm evenly through in-situ polymerization on the surface of the diaphragm, making the surface of the diaphragm smoother and allowing the polymer to be fully distributed between the particles on the surface of the diaphragm, which is beneficial to ensure good contact between the electrolyte and the electrode, thereby facilitating the performance of the battery.
[0145] After testing, the performance of the solid electrolytes in Examples 2 to 8 of the present invention is substantially equivalent to that of the solid electrolyte in Example 1.
[0146] The solid electrolytes in Examples 1 to 8 were assembled into soft-pack batteries, and then a needle puncture test was performed. After the needle puncture test, the soft-pack batteries were observed to see if there were bulging, gas production, or combustion and explosion on the surface. The needle puncture test showed that the soft-pack batteries assembled with the solid electrolytes in the present invention did not have bulging, gas production, combustion or explosion after acupuncture, and had high safety in use.
[0147] In summary, the solid electrolyte in the present invention has a room temperature ionic conductivity and electrochemical stability of up to 0.432mS / cm, and has higher safety and higher energy density than commercial liquid electrolytes. The present invention polymerizes three different monomers of vinyl ethylene carbonate, 2,2,3,4,4,4-hexafluorobutyl methacrylate and triallyl phosphate into a solid electrolyte, which can not only ensure high ionic conductivity, but also achieve a wide electrochemical stability window and non-flammable high safety. At the same time, it can stably match the high-voltage NCM622 positive electrode and the lithium metal negative electrode to achieve high energy density. Importantly, after the assembled soft-pack battery passed the acupuncture test, there was no bulging, gas production or combustion explosion, which further proves that the solid electrolyte in the present invention has excellent safety performance.
[0148] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A solid electrolyte, characterized in that: The invention comprises electrolyte salt and polymer; the raw materials for preparing the polymer comprise ethylene carbonate polymer monomer, fluoroethylene carbonate polymer monomer and ethylene phosphate polymer monomer.
2. The solid electrolyte according to claim 1, characterized in that: The solid electrolyte also includes a separator; the electrolyte salt and the polymer are distributed on the separator; the separator is selected from at least one of a ceramic-coated polypropylene separator, a glass fiber separator, a polypropylene separator, a polyethylene separator, and a cellulose acetate separator.
3. The solid electrolyte according to claim 1, characterized in that: The olefin carbonate polymerization monomer is selected from at least one of vinyl ethylene carbonate, allyl methyl carbonate, allyl ethyl carbonate, diallyl pyrocarbonate, dimethyl allyl carbonate, and vinylene carbonate; And / or, the fluoroalkylene carbonate polymerizable monomer is at least one selected from 2,2,3,4,4,4-hexafluorobutyl methacrylate, allyl perfluoropentanoate, allyl perfluorononanoate, allyl trifluoroacetate, and hexafluorobutyl acrylate; And / or, the phosphate ester polymerization monomer is at least one selected from triallyl phosphate, 2-propylene-diethyl phosphate, and allyl diethyl phosphate.
4. The solid electrolyte according to claim 1, characterized in that: The raw materials for preparing the polymer also include an initiator. Taking the total mass percentage of the carbonate ester polymer monomer, the fluorocarbonate ester polymer monomer and the phosphate ester polymer monomer as 100%, the mass percentage of the initiator is 0.1-1%.
5. The solid electrolyte according to claim 1, characterized in that: The mass of the electrolyte salt is 10-40% of the total mass of the raw materials for preparing the polymer.
6. The solid electrolyte according to any one of claims 1 to 5, characterized in that: The molar ratio of the olefin carbonate polymer monomer, the fluorinated olefin carbonate polymer monomer and the olefin phosphate polymer monomer is 1:(0.05-0.15):(0.1-0.2).
7. The method for preparing a solid electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: mixing the raw materials for preparing the polymer and the electrolyte salt to obtain a precursor solution; S2: heating the precursor solution to perform a polymerization reaction; Alternatively, the precursor solution is loaded on the diaphragm and heated to allow the precursor solution to undergo an in-situ polymerization reaction on the diaphragm.
8. The method for preparing a solid electrolyte according to claim 7, characterized in that: The temperature of the in-situ polymerization reaction is 50 to 80° C. And / or, the in-situ polymerization reaction time is 2 to 12 hours; And / or, the preparation method is carried out under an inert atmosphere with a water content of less than 1 ppm and an oxygen content of less than 1 ppm.
9. A solid-state battery, characterized in that: The solid electrolyte comprises the solid electrolyte according to any one of claims 1 to 6.
10. The solid-state battery according to claim 9, characterized in that: The positive electrode active material of the solid-state battery includes at least one of NCM622, NCM811, and LFP positive electrode materials.